Analysis of Trigonometry Learning Outcomes in the Application of Geogebra-Assisted Jigsaw Methods - Nabil Fachrudin Halim; Moh Mahfud Effendi; Mayang Dintarini (Department of Mathematics Education University of Muhammadiyah Malang, 2023)
In the material of graphs of trigonometric functions, students are expected to be able to draw graphs of their functions which later affect student learning outcomes on the material of graphs of trigonometric functions. The purpose of this study was to analyze the learning outcomes of trigonometry in the application of Geogebra-assisted jigsaw learning. The data collection technique is done by giving test questions with trigonometric function graph material. The test results are used to determine the learning outcomes of the cognitive domain. To obtain learning outcomes in the affective and psychomotor domains, it is done by filling out the observation sheet. The results of this study indicate that the learning outcomes of trigonometry in the application of Geogebra-assisted jigsaw learning at SMAN 1 Kraksaan are very good with an average score of 89.4 on the posttest. Then the affective observation sheet obtained an average of 96.6 and psychomotor 90.5 with a completeness percentage of 86.1%.